2008
DOI: 10.1002/bmc.1000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of major alkaloids and steroidal saponins in rat serum by HPLC‐diode array detection‐MS/MS following oral administration of Huangbai‐Zhimu herb‐pair Extract

Abstract: Huangbai-Zhimu herb-pair (HBZMHP) is a widely used Chinese traditional medicine formula in treating various diseases; however, its active components have remained unknown. In this paper, serum chemistry and combined high-performance liquid chromatography (HPLC), diode-array detection and mass-spectrometry (MS) techniques were used to study the constituents of HBZMHP extract absorbed into rat serum after oral administration. A total of nine characteristic HPLC peaks in the TIC chromatograms were identified as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 29 publications
(23 reference statements)
1
31
0
5
Order By: Relevance
“…Previous pharmacological and phytochemical studies about this herb mainly focused on the quaternary isoquinoline alkaloids (e.g. berberine and palmatine) (Ma et al, 2008;Wu et al, 2005;Mitani et al, 2001;Park et al, 2007), while little attention was paid to the phenols and other compounds (Yoshiteru et al, 1994). Several analytical methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous pharmacological and phytochemical studies about this herb mainly focused on the quaternary isoquinoline alkaloids (e.g. berberine and palmatine) (Ma et al, 2008;Wu et al, 2005;Mitani et al, 2001;Park et al, 2007), while little attention was paid to the phenols and other compounds (Yoshiteru et al, 1994). Several analytical methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although identification of these constituents in rat serum and urine by liquid chromatography-mass spectrometry can be retrieved in the literature [13,14], to our knowledge, several analytical methods have been previously described to determine only one or two of these relevant compounds in plasma separately [15][16][17][18] and none of these methods is able to simultaneously determine all compounds of interest in biological samples. The present study was designed to develop a rapid and sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) with polarity switching and utilize it for full pharmacokinetic investigation of the main active constituents in ZSP following oral administration of its extract.…”
Section: Introductionmentioning
confidence: 99%
“…In the negative ESI-MS mode, the typical ion peak at m/z [M + HCOO−]− could always be observed due to the conjugation of the molecular with the added formic acid in the mobile phase (Zhao et al, 2008). It also indicated that the sugar unite substituted at C-7-O position lost easily, and the ion peaks at m/z [M − 7-O-sugar]− for these fl avonoids always appeared as the (Ma et al, 2008;Hong et al, 1999;Ma et al, 1996;Kang et al, 2006). It was found that the saponins 10 and 11 without any hydroxyl group in their aglycons could be easily detected in the positive ESI-MS chromatogram, while saponins 8 and 9 that have hydroxyl groups in their molecular aglycons were detected in the negative ESI-MS chromatogram in the present study.…”
Section: Identifi Cation Of the Chemical Constituents In Rat Plasmamentioning
confidence: 91%
“…Among them, fi ve alkaloids were unambiguously identifi ed as magnofl orine, menisperine, jatrorrhizine, palmatine and berberine by a direct comparison with those standard compounds. The molecular structures of the alkaloids were deduced from the positive molecular ion peak at m/z [M]+ as well as the corresponding sub-fragments in their MS n spectra (Table 1) (Ma et al, 2008;Hua et al, 2007;Lu et al, 2006;Zhang et al, 2006 O]+ were typical for the aporphine alkaloids (6, 13) in the present study. Another nine phenols were all unambiguously identifi ed by a direct comparison with the reference compounds.…”
Section: Identifi Cation Of the Chemical Constituents In Rat Plasmamentioning
confidence: 99%
See 1 more Smart Citation